Pregnant women with SARS‐CoV‐2 infection are at higher risk of death and pneumonia: propensity score matched analysis of a nationwide prospective cohort (COV19Mx). (1st February 2021) - Martinez‐Portilla, R. J.; Sotiriadis, A.; Chatzakis, C.; Torres‐Torres, J.; Espino y Sosa, S.; Sandoval‐Mandujano, K.; Castro‐Bernabe, D. A.; Medina‐Jimenez, V.; Monarrez‐Martin, J. C.; Figueras, F.; Poon, L. C.
ABSTRACT: Objective: There are limited, unmatched data reporting low complication rates in pregnant women with coronavirus disease 2019 (COVID‐19). The aim of this study was to compare COVID‐19‐related outcomes between pregnant and non‐pregnant women after adjusting for potential risk factors for severe outcomes. Methods: Data were obtained from the COVID‐19 National Data Registry of Mexico, which is an ongoing prospective cohort of people of any age with clinically suspected severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and admitted to 475 monitoring hospitals. This study included pregnant and non‐pregnant women of reproductive age (15–45 years) with COVID‐19 confirmed by reverse transcription polymerase chain reaction. To adjust for underlying risk factors, propensity score matching was conducted for chronic obstructive pulmonary disease, asthma, smoking, hypertension, cardiovascular disease, obesity, diabetes, chronic renal disease, immunosuppression, age, language, nationality and level of health insurance. The primary outcome was death. Secondary outcomes were pneumonia, intubation and intensive care unit (ICU) admission. Results: The cohort comprised 5183 pregnant and 175 905 non‐pregnant women with COVID‐19. The crude (unmatched) rates of death, pneumonia, intubation and ICU admission in pregnant compared with non‐pregnant women were 1.5% vs 1.5%, 9.9% vs 6.5%, 8.1% vs 9.9% and 13.0% vs 6.9%, respectively. After propensity score matching (5183 pregnant and 5183 non‐pregnant matched women), pregnant women had a higher odds of death (odds ratio (OR), 1.84; 95% CI, 1.26–2.69), pneumonia (OR, 1.86; 95% CI, 1.60–2.16) and ICU admission (OR, 1.86; 95% CI, 1.41–2.45) than non‐pregnant women, but similar odds of intubation (OR, 0.93; 95% CI, 0.70–1.25). Conclusion: After adjusting for background demographic and medical factors, pregnancy is a risk factor for death, pneumonia and ICU admission in SARS‐CoV‐2‐infected women of reproductive age. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from the abstract to view the translations. RESUMEN: Las mujeres embarazadas con infección por SARS‐CoV‐2 tienen un mayor riesgo de muerte y de neumonía: análisis por pareamiento por puntaje de propensión de una cohorte prospectiva nacional (COV19Mx) Objetivo: Existen datos limitados y no contrastados que informan de las bajas tasas de complicaciones en mujeres embarazadas afectadas por coronavirus 2019 (COVID‐19). El objetivo de este estudio fue comparar los resultados relacionados con COVID‐19 entre mujeres embarazadas y no embarazadas, después de ajustar los posibles factores de riesgo de resultados graves. Métodos: Los datos se obtuvieron del Registro Nacional de Datos sobre COVID‐19 de México, que es una cohorte prospectiva en curso de personas de cualquier edad con sospecha clínica de infección por coronavirus del síndrome respiratorio agudo grave de tipo 2 (SARS‐CoV‐2) e ingresadas en 475 hospitales con seguimiento. Este estudio incluyó a mujeres embarazadas y no embarazadas en edad reproductiva (15‐45 años) con COVID‐19 confirmado por la reacción en cadena de la polimerasa de transcripción inversa. Para ajustar respecto a los factores de riesgo subyacentes, se realizó un pareamiento por puntaje de propensión para enfermedad pulmonar obstructiva crónica, asma, tabaquismo, hipertensión, enfermedad cardiovascular, obesidad, diabetes, enfermedad renal crónica, inmunosupresión, edad, idioma, nacionalidad y nivel de seguro médico. El resultado primario fue la muerte. Los resultados secundarios fueron la neumonía, la intubación y el ingreso en la unidad de cuidados intensivos (UCI). Resultados: La cohorte consistió en 5.183 mujeres embarazadas y 175.905 no embarazadas, todas con COVID‐19. Las tasas brutas (no pareadas) de muerte, neumonía, intubación e ingreso en la UCI en las mujeres embarazadas, en comparación con las no embarazadas, fueron del 1, 5% frente al 1, 5%, del 9, 9% frente al 6, 5%, del 8, 1% frente al 9, 9% y del 13, 0% frente al 6, 9%, respectivamente. Tras el pareamiento por puntaje de propensión (5.183 mujeres embarazadas y 5.183 no embarazadas pareadas), las mujeres embarazadas tuvieron una mayor probabilidad de muerte (razón de momios [RM], 1, 84; IC 95%, 1, 26–2.69), neumonía (RM, 1, 86; IC 95%, 1, 60–2, 16) e ingreso en la UCI (RM, 1, 86; IC 95%, 1, 41–2, 45) que las mujeres no embarazadas, pero probabilidades similares de intubación (RM, 0, 93; IC 95%, 0, 70–1, 25). Conclusión: Tras ajustar los factores demográficos y médicos subyacentes, el embarazo es un factor de riesgo de muerte, neumonía e ingreso en la UCI en mujeres en edad reproductiva infectadas por el SARS‐CoV‐2. Copyright © 2020 ISUOG. Published by John Wiley & Sons Ltd. 摘要: SARS‐CoV‐2新型冠状病毒感染的孕妇死亡和罹患肺炎的风险更高:一项针对全国前瞻性队列研究(COV19Mx)的倾向评分匹配分析 目的: 有些有限，且不匹配数据报道了孕妇罹患2019冠状病毒(COVID‐19) 的低并发症率。这项研究的目的是在校正严重预后的潜在危险因素后，对孕妇和非孕妇中与COVID‐19相关的预后进行比较。 方法: 数据从墨西哥COVID‐19国家数据注册中心获得，这是一项正在进行的 任何年龄段的临床前瞻性队列研究，其年龄范围广泛，临床疑似新型冠状病毒2(SARS‐CoV‐2)感染并合并严重的急性呼吸系统综合症，并且已入住475家监测医院。这项研究纳入了使用逆转录聚合酶链反应确认为感染COVID‐19的育龄妇女(15‐45岁)包括孕妇和非孕妇。为了调整潜在的危险因素，对慢性阻塞性肺病，哮喘，吸烟，高血压，心血管疾病，肥胖症，糖尿病，慢性肾病，免疫抑制疾病，年龄，语言，国籍和健康保险 水平进行了倾向评分匹配。主要预后为死亡。次要预后为肺炎，插管和入院重症监护(ICU) 。 结果: 该队列由感染COVID‐19 的5183名 的孕妇和175905名非孕妇组成。与 未怀孕的妇女相比，孕妇的死亡率， 肺炎，气管插管和入住ICU比率分别为1.5%比1.5%，9.9%比6.5%，8.1%比9.9%和13.0%比6.9%。(不匹配的原始数据比率)对(5183名孕妇和5183名非孕妇 )进行倾向评分匹配后，孕妇的死亡率 (优势比(OR)为1.84； 95%置信区间，1.26‐2.69)，肺炎(优势比为1.86； 95% 置信区间(1.60–2.16)和ICU入院率(优势比为1.86； 95%置信区间，1.41‐2.45)高于未怀孕的女性，但插管几率相似(优势比为0.93； 95%置信区间，0.70–1.25)。 结论: 在调整了背景人口统计学和医学因素后，怀孕是导致育龄妇女感染新型冠状病毒SARS‐CoV‐2后 死亡，肺炎和入住ICU的危险因素。版权 © 2020 ISUOG。由威利父子公司(John Wiley & Sons Ltd)出版。